Activation of pig oocytes using calcium ionophore: effect of protein synthesis inhibitor cycloheximide - Jílek, F; Hüttelová, R; Petr, J; Holubová, M; Rozinek, J (Animal reproduction science, 2000)
In vitro matured pig oocytes were activated using a combined treatment of calcium ionophore A 23187 with cycloheximide. The oocytes were exposed to ionophore (10, 25 or 50 microM) for 0.5, 1, 3, 5 or 7 min and then cultured with cycloheximide (0 or 10 microg/ml) for 6 h. Cycloheximide treatment significantly increased the activation rate of oocytes and the percentage of oocytes that were able to develop after activation. The highest activation rate was observed after treatment with 50 microM ionophore. The highest percentage of developing eggs was observed after combined treatment of ionophore (25 microM) with cycloheximide. The percentage of oocytes developing up to the morula and blastocyst stage was not significantly increased after cycloheximide treatment.
Keywords: cykloheximid; stadium rýhování vajíčka; Calcimycin; partenogeneze; inhibitory syntézy proteinů; Protein Synthesis Inhibitors; Female; zvířata; Cells, Cultured; oocyty; Swine; ionofory; Cycloheximide; ženské pohlaví; calcimycin; kultivované buňky; Animals; Oocytes; Cleavage Stage, Ovum; prasata; Parthenogenesis; Ionophores